If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3y-2(0)=6
We simplify the equation to the form, which is simple to understand
3y-2(0)=6
Reorder the terms in parentheses
3y+(-0)=6
Remove unnecessary parentheses
+3y-0=+6
We move all terms containing y to the left and all other terms to the right.
+3y=+6
We simplify left and right side of the equation.
+3y=+6
We divide both sides of the equation by 3 to get y.
y=2
| 3x+2y+3z=-15 | | w/2=51 | | 10*q=6.723 | | 12x-y=211x | | 5=u/9 | | g^2-9g-22= | | 2x+3y-z=0 | | 3/x-4=5/x | | 2(6x+4)-15=-2(3x-82) | | -28-2x=12x-7x | | x-2y+2z=-2 | | (4x^2-3x^3)-(9x^2-5x^3)=-3x^6 | | -7w-5-7w+9= | | x^2+1x-420=0 | | (9/(5w))=(7/9) | | -2/3+a=1/9 | | (9/5w)=(7/9) | | 6x+7=5(x+1) | | y=x+(.005*15*x) | | 10x-2.667-4x=6x | | 3x^2+14x-200=0 | | 64=8w | | 5x+11=7x-3 | | 4j=44 | | X^2+y^2=40 | | -m/6=29 | | -1+15= | | 7(a-7)+16=2(a-4) | | s-15=20 | | 3x-0=3 | | -1+14= | | 5-3/8x=-1/7+3x |